Antioxidative Potential and Ameliorative Effects of Rice Bran Fermented with Lactobacillus against High-Fat Diet-Induced Oxidative Stress in Mice - Tingting Yin; Yidan Chen; Wenzhao Li; Tingting Tang; Tong Li; Binbin Xie; Dong Xiao; Hailun He (MDPI AG, 2024)
Rice bran is an important byproduct of the rice polishing process, rich in nutrients, but it is underutilized and often used as feed or discarded, resulting in a huge amount of waste. In this study, rice bran was fermented by Lactobacillus fermentum MF423 to obtain a product with high antioxidant activity. First, a reliable and efficient method for assessing the antioxidant capacity of the fermentation products was established using high-performance liquid chromatography (HPLC), which ensured the consistency of the batch fermentation. The fermented rice bran product (FLRB) exhibited significant antioxidant activity in cells, C. elegans, and hyperlipidemic mice. Transcriptome analysis of mouse livers showed that the expression of plin5 was upregulated in diabetic mice administered FLRB, thereby preventing the excessive production of free fatty acids (FFAs) and the subsequent generation of large amounts of reactive oxygen species (ROS). These studies lay the foundation for the application of rice bran fermentation products.